2009
DOI: 10.1097/mcg.0b013e318181b42f
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Gastric Emptying is Often Abnormal When Solid Emptying is Normal

Abstract: Liquid gastric emptying is commonly abnormal in patients who have normal solid studies. Liquid studies should be routinely performed in addition to solid studies to fully evaluate gastric motility in patients with symptoms suggestive of gastroparesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 25 publications
1
35
0
1
Order By: Relevance
“…Fifty five of these 60 patients did not have diabetes and, hence, represent 16% (55/336) of all non-diabetics and 28% (55/197) of non-diabetic patients with normal solid GES. Zeissman et al has recently reported that assessment of gastric emptying of liquids alone without solid food may provide added information in patient assessment [12,13]. In his studies, in which the liquid GES and solid GES were performed separately but sequentially on the same day, 32% of patients with normal solid gastric emptying had delayed liquid emptying [13].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Fifty five of these 60 patients did not have diabetes and, hence, represent 16% (55/336) of all non-diabetics and 28% (55/197) of non-diabetic patients with normal solid GES. Zeissman et al has recently reported that assessment of gastric emptying of liquids alone without solid food may provide added information in patient assessment [12,13]. In his studies, in which the liquid GES and solid GES were performed separately but sequentially on the same day, 32% of patients with normal solid gastric emptying had delayed liquid emptying [13].…”
Section: Discussionmentioning
confidence: 98%
“…Thus, assessment of gastric emptying of solids and liquids evaluate different aspects of gastric physiology. Recent studies using sequential liquid and solid gastric emptying have reported identification of patients with delayed liquid emptying but normal solid emptying [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In a retrospective analysis from one study, 13 of 17 patients with symptoms of gastroparesis had normal solid gastric emptying but showed delayed liquid gastric emptying. 100 In a prospective followup from the same study, 10 of 30 individuals with symptoms of gastroparesis and normal solid gastric emptying showed delayed liquid gastric emptying. In another study of 101 individuals with sus pected gastroparesis, delays in solid gastric emptying were found in 16% of individuals, whereas delayed liquid gastric emptying was detected in 32%.…”
Section: Diagnosis Of Presumed Gastroparesismentioning
confidence: 95%
“…One method begins with a 30-min liquid-only study followed by the solid study (5,6). The other approach is to simultaneously administer the dual-isotope solid and liquid meal (7).…”
Section: Discussionmentioning
confidence: 99%